The Effect of Liquid Organic Fertilizer of Shallot Skins and Compost of Coconut Dregs on the Growth of Mint Plant (Mentha piperita L.) Cuttings - Shahra, Farah Diba; Jayanthi , Sri; Atmaja, Teuku Hadi Wibowo (Jurnal Pijar Mipa, 2024)
Mint (Mentha piperita L.) belongs to the Lamiaceae family, whose essential oil is used as a flavouring agent and to treat diseases. The low productivity of mint plants is because the nutrients in the planting medium do not support growth efforts made through fertilization. Two organic materials that can be used as fertilizer are shallot skin and coconut dregs. This study aimed to determine the effect of liquid organic fertilizer on shallot skins and coconut dregs compost and the most optimal treatment for the growth of mint plant cuttings (Mentha piperita L.). This type of research was quantitative with an experimental method using a completely randomized design (CRD) factorial consisting of 2 factors, namely red onion skin liquid organic fertilizer and coconut dregs compost, each consisting of 3 levels so that the treatment combination consisted of 9 treatments with as many repetitions as three times. Data analysis in this study used the Kruskal Wallis test with SPSS. The results showed that it had a very significant effect on wet weight and a significant effect on the number of leaves on the growth of mint cuttings (Mentha piperita L.). The best treatment for each observation parameter was wet weight BM1AK2 (13 grams), number of primary branches BM1AK2 (2.67), plant height BM2AK1 (26.5 cm) and number of leaves BM2AK1 (27.33 strands).